Antiretroviral resistance, genotypic characterization and origin of Human Immunodeficiency Virus among the infected wives of Intravenous drug users in Manipur - Sharma, Adhikarimayum Lakhikumar (Sci Rep, 2018)
Increasing incidence of drug resistance is ascertained to be the main obstacles in limiting the virus among the human immunodeficiency virus (HIV) infected individuals. This study investigates the drug resistance mutations (DRMs), genetic variants and origin of transmitted drug resistance of HIV-1 among the HIV-1 infected wives of intravenous drug users (IDUs) in Manipur. 44 HIV pol gene sequences were generated from 56 blood samples by viral gene amplification and sequencing. Sequences were then analysed for drug resistance, genetic variants and origin. The result revealed that among the treatment naive cases, 35.7% had Transmitted Drug Resistance Mutations (TDRMs) while among treatment experienced cases, 50% had Acquired Drug Resistant Mutations (ADRMs). These TDRMs and ADRMs conferred resistance to nucleoside reverse transcriptase inhibitors (NRTIs), non-nucleoside reverse transcriptase inhibitors (NNRTIs) and/or protease inhibitors (PIs). Majority of the isolated HIV-1 sequences (77.3%) were subtype C while 9.1% was discordant subtype, 6.8% was subtype B, 4.5% was CRF_01AE and 2.3% was URF_BC. TDRM strains were found to be introduced from Myanmar, Vietnam and mainland India. This study also reveals the appearance of CRF_01AE for the first time in Manipur. The finding of this study indicates high prevalence of drug resistant mutations and complex molecular epidemiology in Manipur.